1999
DOI: 10.1104/pp.120.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Metabolism in Pea Seedlings. A Comparison ofd-Glucosone, l-Sorbosone, andl-Galactono-1,4-Lactone as Ascorbate Precursors1

Abstract: 14 C]Glc incorporation into AsA, this does not mean that it is not a precursor, because competition between endogenous and exogenous pools was minimized by its very small pool size and rapid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 34 publications
8
54
0
4
Order By: Relevance
“…Arrows represent proteins identified by mass spectrometry. decrease oxidative damage during seed development and germination (Pallanca & Smirnoff, 1999;De Gara et al, 2003) and provide antioxidant defense when acquiring desiccation tolerance (Baily et al, 2001). Among the AsA-glutathione cycle enzymes, DHAR had the highest increase in percentage during seed development (De Gara et al, 2003).…”
Section: Genotype-specific Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrows represent proteins identified by mass spectrometry. decrease oxidative damage during seed development and germination (Pallanca & Smirnoff, 1999;De Gara et al, 2003) and provide antioxidant defense when acquiring desiccation tolerance (Baily et al, 2001). Among the AsA-glutathione cycle enzymes, DHAR had the highest increase in percentage during seed development (De Gara et al, 2003).…”
Section: Genotype-specific Proteinsmentioning
confidence: 99%
“…Among the AsA-glutathione cycle enzymes, DHAR had the highest increase in percentage during seed development (De Gara et al, 2003). Because there is shortage of AsA in seeds (Arrigoni et al, 1992), DHAR activity during early seed germination can protect the small AsA pool from oxidation (Pallanca & Smirnoff, 1999). It has also been suggested that the cold-regulated proteins are involved in the cryoprotection of the plasma membrane against freezing and dehydration-induced stress (Kreps et al, 2002;Garwe et al, 2003).…”
Section: Genotype-specific Proteinsmentioning
confidence: 99%
“…It was suggested that these legume seeds lost significant amounts of VC during the dehydration process (see Table 1). Pallanca and Smirnoff reported that the total VC content of pea seedlings significantly increased between 24 and 50 h after soaking although the AsA is oxidized and destroyed during the desiccation phase of seed development (2).…”
Section: Changes In Vc Content Of Legume Seeds After Soaking In Watermentioning
confidence: 99%
“…Chloroform/phenol mixture (500 mL, 1:1) was added and mixed, and the mixture was centrifuged at 15,000 rpm for 5 min at 23 C. The supernatant was transferred to a new Eppendorf tube, and 2.5 volumes of ethanol were added to precipitate the genomic DNA. The samples were centrifuged at 15,000 rpm for 5 min at 23 C. The DNA pellet was washed with 1 mL of the 70% ethanol and dried in a vacuum pump for 5 min. Finally, the DNA pellet was dissolved in 20 mL of the TE buffer (10 mM Tris, 1 mM EDTA, pH 8.0) and stored at À20 C.…”
Section: Methodsmentioning
confidence: 99%
“…23) In this study, we focused on the expression status of the VTC2 and VTC5 genes during the early seedling stages of A. thaliana. We analyzed the total AsA levels of A. thaliana wild-type and the AsA deficient mutants at various stages of development, and measured the expression levels of the two genes.…”
mentioning
confidence: 99%